Genes in food – why the furore?. (1st April 2003) - Dixon, B.
Abstract : Although unprecedented and perhaps unique in its irrationality, the recent furore over genetically modified (GM) food holds extremely important lessons for scientists. Some sections of the media undoubtedly bear a heavy responsibility for giving the expression 'GM' threatening connotations that are quite unwarranted. However, influential contributions to the hysteria have come from a surprising range of other sources, including some scientists. The research community has failed in its responsibility to society in three ways. Firstly, plant scientists did not appreciate that certain techniques (such as the use of antibiotic resistance genes as markers during plant transformation) would inevitably provoke public consternation. As a result, they took no steps to address such concerns. Secondly, researchers overlooked, minimized or in some cases simply dismissed the significance of public fears that they were 'interfering with Nature' or 'playing God'. Thirdly, plant breeders apparently saw no need to take pro-active measures with regard to the media and public in placing potential environmental and nutritional benefits of GM crops on the agenda in a positive fashion. Partly because of this failure, GM food is now firmly established in the public mind as wholly objectionable. One measure of how far we have travelled down that road is that it hardly matters any more whether objections are based on alleged environmental risks of cultivating GM crops or alleged toxicological hazards of eating them. 'Genetically modified organism', like 'radioactivity', has become an odious, generic shibboleth. Given that millions of people throughout the world are already benefiting from pharmaceuticals made by GM organisms, this is bizarre.